Melatonin improves in vitro maturation and subsequent embryo development of caprine oocytes* - AGARWAL, SURBHI; KHARCHE, S D; BHATIYA, A K (The Indian Journal of Animal Sciences, 2018)
The aim of the present investigation was to study the effect of melatonin on in vitro maturation and subsequent embryo development of caprine oocytes. In experiment 1, 384 in vitro matured oocytes were selected and randomly divided in to two groups, viz. group 1 (control) wherein oocytes matured in maturation media without supplementation for 27 h in humidified atmosphere at 38.5°C with 5% CO2 in CO2 incubator while in group 2 oocytes matured in maturation media with 30 ng/ml melatonin supplementation. After 27 h of culture, nuclear maturation was observed in both groups using Hoechst dye. In experiment 2, 1,336 oocytes were randomly divided into two groups, viz. group 1 (641) wherein oocytes were matured in maturation media without melatonin while in group 2 (n=695) oocytes matured in maturation media with 30 ng/ml melatonin supplementation. After 27 h, oocytes of both groups were then subjected to in vitro fertilization.The rate of nuclear maturation in group 2 (30 ng/ml melatonin) was significantly higher than that of group 1 (control). Similarly, the cleavage rate and blastocyst formation from in vitro matured goat oocytes were significantly higher in group 2 than that of group 1. In conclusion, the result indicated that the supplementation of 30 ng/ml melatonin in maturation media improves the nuclear maturation and subsequent cleavage rates and blastocyst production from caprine oocytes.